Parathyroid carcinoma - Filipović Aleksandar; Paunović Ivan; Savjak Dragutin; Živković Tamara (Vojnosanitetski Pregled)
Background. Parathyroid carcinoma is the least frequent malignancy among endocrine tumors. In the most reported series of patients with primary hyperparathyroidism the incidence of carcinoma is less than 1%. Recognition by a surgeon that the parathyroid tumor is malignant, and the performance of an adequate en bloc removal of primary lesion, with histologic diagnosis offer the best treatment of a patient with this unusual malignancy. Case report. We reported a 30-year-old patient with parathyroid carcinoma, primary hyperparathyroidism, and recurrent nephrocalcinosis. Marked hypercalcemia, low serum phosphorus, and substantial elevation of serum parathyroid hormone indicated a diagnosis of primary hiperparathyroidism. General symptoms were anorexia, muscle weakness, back pain and depression. Ultrasonography done before the surgery revealed a 2 cm upper left parathyroid gland with solid and cystic areas. The neck exploration was done with en block resection of the tumor. A histopathological evaluation confirmed the diagnosis of parathyroid carcinoma. Over more than a three-year-follow-up, the patient had no evidence of the disease recurrence and his serum PTH and calcium levels remained within the normal. Conclusion. Parathyroid carcinoma is a rare cause of primary hyperparathyroidism. Preoperative diagnosis remains a challenge. Radical en bloc resection of the tumor is the treatment of choice for this malignancy.